2021
DOI: 10.1186/s13071-021-04896-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple diagnostic tests demonstrate an increased risk of canine heartworm disease in northern Queensland, Australia

Abstract: Background Canine heartworm (Dirofilaria immitis) is a life-threatening infection of dogs with a global distribution. Information on the prevalence of D. immitis and associated risk factors for canine heartworm antigen positivity—and thus disease—in Australia is scarce or outdated. The current reference method for D. immitis diagnosis in dogs is via the detection of heartworm antigen in blood using commercially available microwell-based enzyme-linked immunosorbent assays (ELISAs). Heat treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 47 publications
0
15
2
Order By: Relevance
“…Even though molecular techniques present some limitation, these methods can provide a rapid, sensitive, and accurate diagnoses, and prevent the occurrence of false-positive results due to cross-reactivity. Several studies have reported the use of molecular approaches targeting conserved DNA regions in the diagnosis of numerous filarial nematodes ( Laidoudi et al, 2020a , 2020b ; Panetta et al, 2021 ; Rishniw et al, 2006 ). As expected, with the present study the real-time PCR technique had a higher positive rate than conventional PCR and seems to be an alternative diagnostic method for detecting D .…”
Section: Discussionmentioning
confidence: 99%
“…Even though molecular techniques present some limitation, these methods can provide a rapid, sensitive, and accurate diagnoses, and prevent the occurrence of false-positive results due to cross-reactivity. Several studies have reported the use of molecular approaches targeting conserved DNA regions in the diagnosis of numerous filarial nematodes ( Laidoudi et al, 2020a , 2020b ; Panetta et al, 2021 ; Rishniw et al, 2006 ). As expected, with the present study the real-time PCR technique had a higher positive rate than conventional PCR and seems to be an alternative diagnostic method for detecting D .…”
Section: Discussionmentioning
confidence: 99%
“…Canine heartworm disease is a potentially deadly cardiopulmonary disease caused by the mosquito-borne filarial nematode Dirofilaria immitis , which is distributed across many parts of the world ( Simón et al, 2012 ; Genchi and Kramer, 2020 ; Lau et al, 2021 ; Noack et al, 2021 ). Although the prevalence of D. immitis in Australia is low, the parasite is endemic to the country and has recently re-emerged in dogs in Queensland ( Nguyen et al, 2016 ; Orr et al, 2020 ; Panetta et al, 2021 ). For the past 30 years in Australia and the USA, the main strategy for canine heartworm prevention has been the administration of macrocyclic lactone (ML) anthelmintics ( Orr et al, 2020 ; Diakou and Prichard, 2021 ; Lau et al, 2021 ; Noack et al, 2021 ; Prichard, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of MLs over the past 30 years has successfully reduced the prevalence of canine heartworm infection (Orr et al, 2020; Lau et al, 2021). However, the re-emergence of D. immitis infection in Queensland, Australia and the confirmation of ML-resistant isolates in the USA poses an important question of whether ML-resistance exists in Australia (Blagburn et al, 2011; Pulaski et al, 2014; Bourguinat et al, 2015; Blagburn et al, 2016; Nguyen et al, 2016; Maclean et al, 2017; McTier et al, 2017b; Orr et al, 2020; Panetta et al, 2021). By considering microfilariae counts as the phenotype and genotypic tests adopted from the USA, this study did not unequivocally demonstrate the presence of ML-resistant D. immitis in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…The eluted DNA was stored at -20°C until further use in the qPCR and next generation sequencing (NGS) assays. A qPCR targeting the partial canine glyceraldehyde3-phosphate dehydrogenase (GAPDH) region was performed to verify the presence of dog DNA using primers with a probe, as previously described (Orr et al, 2020;Panetta et al, 2021) (Supplementary Table S1). A diagnostic TaqMan probe qPCR targeting the cox1 gene was performed to detect D. immitis DNA using primers with a probe, as previously described (Panetta et al, 2021) (Supplementary Table S1).…”
Section: Dna Isolationmentioning
confidence: 99%
See 1 more Smart Citation